1983
DOI: 10.1128/iai.39.1.423-430.1983
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of protective immunity against murine salmonellosis induced by killed vaccine

Abstract: Swiss-Webster mice were vaccinated with heat-killed salmonellae and then were infected with virulent Salmonella typhimurium. Only 1 of the 18 vaccinated mice died from a challenge of 104 x the 50% lethal dose, and about 70% of them survived a challenge of 105 x the 50% lethal dose. Histopathological examinations of the lesions developed in these vaccinated mice showed that they followed the characteristic features of a primary lesion in murine salmonellosis. There was an early necrosis with infiltration of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…A thorough search of the literature reveals that there is no satisfactory experimental evidence to show unequivocably the survival or multiplication of virulent salmonellae within host macrophages. Histopathological evidence derived from lesions in the liver and spleen of infected mice Hsu, 1980 and1983) further demonstrates that the early stage of a primary lesion and of lesions in infected mice protected by killed salmonella vaccine is characterised by the rapid accumulation of polymorphs, not macrophages. Collectively, therefore, the classification of salmonellae as facultative intracellular bacteria is untenable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A thorough search of the literature reveals that there is no satisfactory experimental evidence to show unequivocably the survival or multiplication of virulent salmonellae within host macrophages. Histopathological evidence derived from lesions in the liver and spleen of infected mice Hsu, 1980 and1983) further demonstrates that the early stage of a primary lesion and of lesions in infected mice protected by killed salmonella vaccine is characterised by the rapid accumulation of polymorphs, not macrophages. Collectively, therefore, the classification of salmonellae as facultative intracellular bacteria is untenable.…”
Section: Discussionmentioning
confidence: 98%
“…The evidence presented here, therefore, lends further support to the previous work from this laboratory (Hsu and Mayo, 1973;Marecki et al, 1975; Mayo e t a f . , 1977; Hsu, 1980 and1983) which showed that salmonellae have erroneously been described as facultative intracellular bacteria (Suter and Ramseier, 1964;Collins, 1974). A thorough search of the literature reveals that there is no satisfactory experimental evidence to show unequivocably the survival or multiplication of virulent salmonellae within host macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Using a transparent zebrafish embryo model that enabled the movements of bacteria and host cells to be observed by microscopy in vivo , mycobacteria were found to enhance macrophage recruitment to nascent granulomas and promote the egress of newly infected cells from the primary granuloma to form secondary lesions (Davis and Ramakrishnan, 2009). Given that granuloma‐like structures have also been described in the liver and spleen of Salmonella‐ infected mice (Nakoneczna and Hsu, 1983) and humans (Mert et al ., 2004), it will be interesting to investigate whether similar activities might also occur during Salmonella pathogenesis. Indeed, it is possible that the motility of infected cells could be affected by the SPI‐2 effector SrfH (Worley et al ., 2006).…”
Section: Colonization Of Systemic Sitesmentioning
confidence: 99%
“…Il has long been held ihal the virulence of salmonellae is directly related to the somalic antigens of the pathogen [10]. We have also established tbat the protective immunity can be induced by ibe killed salmonellae [2] or iheir somalic fragments [3] and that the effective antigen resides wilhin the detoxified LPS of the pathogen [4J. Hence, lhe heat-labile H-anligen is unlikely to function as the primary protective antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The avirulent strain RIA was used as the live vaccine. The healkilled vaccine was prepared by healing a suspension of the virulent strain SR-11 in a boiling water bath for 30 min as previously described [2].…”
Section: Salmonella Vaccinesmentioning
confidence: 99%